The hand grasps the center, while the eyes saccade to the top of novel objects - Juravle, Georgiana; Velasco, Carlos; Salgado-Montejo, Alejandro; Spence, Charles (Frontiers in Psychology, 2015)
In the present study, we investigated whether indenting the sides of novel objects (e.g., product packaging) would influence where people grasp, and hence focus their gaze, under the assumption that gaze precedes grasping. In Experiment 1, the participants grasped a selection of custom-made objects designed to resemble typical packaging forms with an indentation in the upper, middle, or lower part. In Experiment 2, eye movements were recorded while the participants viewed differently-sized (small, medium, and large) objects with the same three indentation positions tested in Experiment 1, together with a control object lacking any indentation. The results revealed that irrespective of the location of the indentation, the participants tended to grasp the mid-region of the object, with their index finger always positioned slightly above its midpoint. Importantly, the first visual fixation tended to fall in the cap region of the novel object. The participants also fixated for longer in this region. Furthermore, participants saccaded more often, as well saccading more rapidly when directing their gaze to the upper region of the objects that they were required to inspect visually. Taken together, these results therefore suggest that different spatial locations on target objects are of interest to our eyes and hands.